2014
DOI: 10.1111/opn.12052
|View full text |Cite
|
Sign up to set email alerts
|

‘It's the little things that count’. Families' experience of roles, relationships and quality of care in rural nursing homes

Abstract: A number of programmes and initiatives already exist to enhance the quality of life of older people in care homes and their families. Serious consideration should be given to more widespread uptake of these initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(91 citation statements)
references
References 38 publications
6
84
0
1
Order By: Relevance
“…The results may also be interpreted as indicating that nursing home management could possibly influence the perceived quality of care by systematically planning for and performing activities that can provide residents and relatives with the little extra things that give meaning in everyday life and facilitate hospitable attitudes towards residents and relatives to make them feel welcomed and respected. Expanding previous findings on relatives’ experiences of quality of care in nursing homes (Ryan & McKenna, ), the current findings thus provide support for nursing home staff and management to improve the quality of care by using aspects of a person‐centred climate.…”
Section: Discussionsupporting
confidence: 75%
“…The results may also be interpreted as indicating that nursing home management could possibly influence the perceived quality of care by systematically planning for and performing activities that can provide residents and relatives with the little extra things that give meaning in everyday life and facilitate hospitable attitudes towards residents and relatives to make them feel welcomed and respected. Expanding previous findings on relatives’ experiences of quality of care in nursing homes (Ryan & McKenna, ), the current findings thus provide support for nursing home staff and management to improve the quality of care by using aspects of a person‐centred climate.…”
Section: Discussionsupporting
confidence: 75%
“…This familiarity was further influenced by a high degree of social capital and an efficient ‘ grapevine ’, (an informal person-to-person means of communication) which appeared to thrive in these small rural communities. As other aspects of the study (pertaining to research questions 2, 3 and 4) have been reported elsewhere [25,26], the findings presented in this paper will focus specifically on the core category that emerged from the study and the impact of familiarity on the choice of home and the success of the transition from the perspective of the family carers.…”
Section: Resultsmentioning
confidence: 99%
“…The second theme was connections and relationships with co‐residents, staff and families which had the potential to facilitate and inhibit transition. Bradshaw, Playford, and Riazi () similarly reported that meaningful relationships with co‐residents and staff are important for a good care home life, as are relationships between residents, staff and families (Davies, ; Ryan & McKenna, ). Continuing valued relationships and beginning new relationships was identified by Brownie et al () as a factor that facilitated adjustment for older people and our findings corroborate this but from the perspective also of staff and families.…”
Section: Discussionmentioning
confidence: 99%